Disrupsi Teknologi dalam Perspektif Hukum - Firdausi, Kamalia; Mewahni, Rizkina (Jurnal Kepastian Hukum dan Keadilan, 2025)
The rapid development and advancement of technology is a matter that has a major impact on social change in today's society. Communication and information technology has been transformed into a community need and its presence has been integrated with the life of the community itself. As a result of the development of communication and information technology, it can be said that there are no more boundaries as a result of the flow of information. The development and advancement of technology brought many changes in the social fabric of society. These changes unconsciously brought society into a new era known as the era of disruption. Disruption filled with new innovations brings society to a new social order that is very different from what has happened before. The development of disruption in the technology sector poses a challenge in itself to the application of the law. The new innovations that appear in the era of disruption are very new and different, so that there must be a struggle between law and disruption itself. This paper will discuss the sociological view of law on technological disruption. Where in the end the law itself has not been able to position itself in the midst of the current of disruption.